Intimate partner violence against women in Maputo city, Mozambique - Zacarias Antonio Eugenio; Macassa Gloria; Svanström Leif; Soares Joaquim JF; Antai Diddy (BMC, 2012)
Abstract Background There is limited research about IPV against women and associated factors in Sub-Saharan Africa, not least Mozambique. The objective of this study was to examine the occurrence, severity, chronicity and "predictors" of IPV against women in Maputo City (Mozambique). Methods Data were collected during a 12 month-period (consecutive cases, with each woman seen only once) from 1,442 women aged 15-49 years old seeking help for abuse by an intimate partner at the Forensic Services at the Maputo Central Hospital, Maputo City, Mozambique. Interviews were conducted by trained female interviewers, and data collected included demographics and lifestyle variables, violence (using the previously validated Revised Conflict Tactics Scale (CTS2), and control (using the Controlling Behaviour Scale Revised (CBS-R). The data were analysed using bivariate and multivariate methods. Results The overall experienced IPV during the past 12 months across severity (one or more types, minor and severe) was 70.2% (chronicity, 85.8 ± 120.9).a Severe IPV varied between 26.3-45.9% and chronicity between 3.1 ± 9.1-12.8 ± 26.9, depending on IPV type. Severity and chronicity figures were higher in psychological aggression than in the other IPV types. Further, 26.8% (chronicity, 55.3 ± 117.6) of women experienced all IPV types across severity. The experience of other composite IPV types across severity (4 combinations of 3 types of IPV) varied between 27.1-42.6% and chronicity between 35.7 ± 80.3-64.9 ± 110.9, depending on the type of combination. The combination psychological aggression, physical assault and sexual coercion had the highest figures compared with the other combinations. The multiple regressions showed that controlling behaviours, own perpetration and co-occurring victimization were more important in "explaining" the experience of IPV than other variables (e.g. abuse as a child). Conclusions In our study, controlling behaviours over/by partner, own perpetration, co-occurring victimization and childhood abuse were more important factors in "explaining" sustained IPV. More investigation into women's IPV exposure and its "predictors" is warranted in Sub-Saharan Africa, particularly Mozambique.